Enzymes in juice processing: a review - Ribeiro, Daniele S.; Henrique, Stella M. B.; Oliveira, Luciene S.; Macedo, Gabriela A.; Fleuri, Luciana Francisco [UNESP] (Wiley-Blackwell Publishing, Inc, 2010)
P>The use of enzymes in juice industry has contributed in increasing the yield and production of various types of juices. The addition pectinases aims in particular to degrade the pectic substances, in the cell wall and middle lamella of the cells of plants, aiming to minimise the impacts of these compounds on the characteristics of the final product, such as colour, turbidity and viscosity. Enzymes able to remove bitterness of citrus juice, extract pigments, among other applications, have also had great interest in the juice industry.
Keywords: Amylase; applications; fruit; industry; juices; laccase; naringinase; oxireductase; pectinases; phenolase